(untitled) (PRÁXIS EM SAÚDE, 2026)
The article presents an experience report in Occupational Therapy carried out in the Amazon, in urban, riverside, and quilombola contexts, involving neurodivergent adolescents (Autism Spectrum Disorder – ASD and comorbidity with Intellectual Developmental Disorder – IDD). The general objective of this article is to report the role of Occupational Therapy in promoting autonomy and expanding functional capacities in daily activities, considering territorial singularities. This intervention was conducted in a multidisciplinary inclusive clinic. The process included an initial assessment of occupational performance using the instruments (AOTA, COPM), territory analysis, and shared goal setting. Strategies were employed that resulted in progress in money recognition and decision-making regarding values and payments, despite geographical barriers and limited access to goods. The experience highlights the relevance of client-centered and socioculturally contextualized Occupational Therapy in fostering participation and independence in instrumental activities of daily living within Amazonian realities.